Single-cell RNA sequencing reveals extensive fibrotic remodeling and pathogenic chondrocyte subpopulations in developmental dysplasia of the hip - Nijiati, Yaxier; Song, Jun; Huang, Peng; Lin, Zichen; Pei, Yingzhi; Ning, Bo (Translational Pediatrics, 2026)
Developmental dysplasia of the hip (DDH) is a common pediatric orthopedic disorder that predisposes affected children to early-onset osteoarthritis (OA), yet the cellular heterogeneity and fibrotic remodeling of acetabular cartilage are poorly understood. Here, we performed single-cell RNA sequencing (scRNA-seq) on acetabular cartilage obtained from three children with DDH and two age-matched controls, thereby generating a transcriptomic atlas of 10,550 chondrocytes. Nine chondrocyte subpopulations were identified, including four previously unrecognized subsets (C1–C4). Compared with controls, DDH cartilage exhibited a marked shift toward fibrocartilage-like phenotypes, characterized by upregulation of fibrotic and matrix-remodeling genes, such as COL1A1, COL1A2, COL3A1, POSTN, MMP13, and MMP14, together with downregulation of key cartilage matrix genes, including COL2A1, ACAN, CHAD, and CNMD. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed enrichment of extracellular matrix (ECM) organization, focal adhesion, apoptosis-related pathways, and metabolic alterations across DDH-associated subsets. Pseudotime analysis demonstrated a trajectory from homeostatic C2 and hypertrophic chondrocytes (HTC) populations toward fibrotic chondrocytes (FC1/FC2) and proliferative dividing chondrocytes (DivC) states, suggesting a progressive degenerative program. CellChat analysis further identified enhanced collagen and TGF-β-mediated signaling among fibrotic subsets. These transcriptional findings were validated by quantitative polymerase chain reaction (PCR), immunohistochemistry (IHC), and histological staining, confirming increased collagen deposition, ECM disorganization, and reduced chondrocyte density in DDH cartilage. Collectively, this study delineates the single-cell landscape of acetabular chondrocytes in DDH and identifies fibrosis-associated pathogenic subpopulations that may contribute to early degenerative changes. These findings highlight potential translational targets for preserving joint integrity and delaying OA progression in children with DDH.